Aspectos relacionados com o uso de parasitoides no manejo integrado da mosca minadora no meloeiro - Silva, Francisco Edivino Lopes da (Universidade Federal Rural do Semi-Árido, 2016)
The melon (Cucumis melo L.) is one of the main cucurbits grown in northeastern Brazil. Among the main obstacles to the production of melon, the leafminer Liriomyza sativae (Diptera: Agromyzidae) stands out as one of the main pests. Since the discovery of natural enemies Opius scabriventris (Hymenoptera: Braconidae) and Neochrysocharis sp. (Hymenoptera: Eulophidae) in melon production areas RN and CE, increased the prospects of the use of biological control in this region. However, information on the preferred instar and competition among parasitoids Opius scabriventris and Neochrysocharis sp. still are scarce. Furthermore, the conservation of these parasitoids in agrosystem is of fundamental importance to the MIP, therefore, it is necessary to know the action of plant protection products on O. scabriventris and Neochrysocharis sp. Therefore, the objective of this study was to define the preferred instar O. scabriventris and Neochrysocharis sp., Evaluate the competition between these two species and the toxicity of insecticides used in melon crop on these two parasitoids in laboratory conditions. To determine the preferred instar were exposed leafminer larvae first, second and third instar for the two species of parasitoids. The competition studies were to assess the simultaneous parasitism O. scabriventris x Neochrysocharis sp. in proportions of 1x1, 2x1, 1x2 for the second and third larval instar L. sativae. The toxicity of insecticides to parasitoids were evaluated in bioassays through contact of parasitoids with freshly contaminated surface. The treatments were: abamectin, clorantraniliprole, cyromazine, espinetoram, spinosad and distilled water (control). Later, with the parasitoids that survived the tests of toxicity were evaluated sublethal effects of pesticides that caused lower mortality on the parasitism capacity. Regarding prefered instar tests, O. scabriventris preferably parasitized second instar larvae, while Neochrysocharis sp. preferred third instar larvae. Regarding competition assays, it was found that parasitoids O. scabriventris and Neochrysocharis sp. competed for larvae second and third instar L. sativae. Regarding toxicity tests, the abamectin, espinetoram and spinosad were the most toxic to the parasitoid O. scabriventris and Neochrysocharis sp. The clorantraniliprole and cyromazine insecticide caused reduction in parasitism capacity of O. scabriventris
Aspects related to the use of parasitoids in the integrated management of leafminer in the melon
Keywords: Melão; Controle biológico; Manejo Integrado de Pragas (MIP); Melon; Biological control; Integrated Pest Management (IPM); CIENCIAS AGRARIAS::AGRONOMIA::FITOTECNIA